2018
DOI: 10.1080/09674845.2017.1399572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-27a, miR-196a2 and miR-146a polymorphisms on the risk of breast cancer

Abstract: Background microRNAs (miRNAs) are potentially involved in many physiopathological processes, including regulation of cell growth, differentiation, apoptosis and cancer. Single nucleotide polymorphisms of the genes encoding miRNAs can alter their expression and may influence cancer risks. This case-control study explored the relationship between three microRNA polymorphisms (miR-27a, miR-196a2 and miR -146a) and breast cancer (BC). Methods A total of 353 breast cancer cases and 353 controls were genotyped for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
5
21
1
Order By: Relevance
“…Their analysis, similar to our research, showed no significant relationship between miRNAs 146aG/C (rs2910164) polymorphism and breast cancer susceptibility in Azeri ethnicity in Iran (Nejati-Azar et al, 2017). The latter, however, indicated that the CC homozygous genotype of miR-146a (rs2910164) was seen in 45 (12.7%) patients with breast cancer and could be related to breast cancer in Rasht ethnicity in Iran (Mashayekhi et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Their analysis, similar to our research, showed no significant relationship between miRNAs 146aG/C (rs2910164) polymorphism and breast cancer susceptibility in Azeri ethnicity in Iran (Nejati-Azar et al, 2017). The latter, however, indicated that the CC homozygous genotype of miR-146a (rs2910164) was seen in 45 (12.7%) patients with breast cancer and could be related to breast cancer in Rasht ethnicity in Iran (Mashayekhi et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, a research by Hu et al, (2009) did not indicate an association between this SNP and the risk of breast cancer in Chinese women. More recently, two studies were dedicated to the relationship of this polymorphism and the breast cancer among different ethnicities of the Iranian population (Nejati-Azar et al, 2017;Mashayekhi et al, 2018). The former analyzed the association of miRNAs 146aG/C (rs2910164) polymorphism with the risk of breast cancer between case and control groups of Azeri ethnicity women in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The full texts of the remaining 79 records were evaluated and 10 articles were excluded for the following reasons: insufficient reported data ( n : 4) [16,17,18,19], studying other genes or polymorphisms ( n : 3) [20,21,22], not a case-control design ( n : 2) [23,24], and a duplicate study ( n : 1) [25]. Finally, a total of 69 articles remained [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85<...>…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SEPP1 A allele was linked with higher breast cancer risk, pointing to the possible use of these SNPs in routine screening. Mashayekhi et al [22] also investigated breast cancer, looking at miR-27a, mir-196a2 and miR-146a in 353 cases and 353 controls. The principle finding was that the CC genotype of miR-146a (rs2910164) was seen in 45 (12.7%) patients with breast cancer and 18 (5.1%) controls (OR 4.09 [95% CI 2.19-7.67] P < 0.001) whilst the minor allele G of miR-27a was associated with a decreased risk of breast cancer (OR 0.24 [95% CI 0.14-0.42] P < 0.001) suggesting that these variants contribute to breast cancer and so may also, one day, be used in a routine setting.…”
Section: Cellular Sciencesmentioning
confidence: 99%
“…Auto-immune Autoantigen [21] SEPP1 and SEP 15 Breast Carcinoma DNA mutation [35] Genes linked to E. coli virulence Kidney Infections DNA mutation [31] miR-146b Thyroid Papillary cancer DNA mutation [18] P53 and miR-34b/c Colon Autoimmune Autoantigen [43] sMICA Lung Carcinoma DNA mutation [38] H. pylori genes Stomach Infection H. pylori [46] CA125, ferritin Ovary Cancer DNA mutation [54] Neutrophil/lymphocyte ratio, CRP, LFTs Liver Infection Various microbes [22] miR-27a, miR-196a, miR-146a Breast Cancer DNA mutation [13] miR-126, miR-210 Heart Atherosclerosis, diabetes Thrombosis, hyperglycaemia [47] S100A4 (metastatin) Ovary Cancer DNA mutation [23] p21 Brain Meningioma DNA mutation [36] 16S-23s RNA region Not applicable Infection S. pneumoniae [42] sMICA, PSA Prostate Cancer DNA mutation [37] Bacterial identification Not applicable Infection P. aeruginosa, B. cenocepacia [39] Genes in H. pylori and parasites Bowel Infection DNA mutation [52] Genes in HPV Anus and genitals Infection DNA mutation [51] Haemostasis The eye Atherosclerosis, diabetes Thrombosis, Hyperglycaemia [48] CEA, CA19-9, cytokeratin-1, mucin-1 Colon Cancer DNA mutation [50] LFTs, platelets Liver Fibrosis Hepatitis B virus [21] Detection of foetal DNA Not applicable Chromosome trisomy DNA mutation [14] SNPs in KCNJ11 and SDF-1β Not applicable Diabetes DNA mutation [16] Serum relaxin-2, PSA Prostate Cancer DNA mutation [17] Serum prolidase and SNP in prolidase Ovary Polycystia Endocrine [55] SNP in IL28B Liver Infection Hepatitis C virus [15] SNPs in TLR4 Kidney, Arteries Diabetes DNA mutation [25] SNPs in GST Cervix Cancer DNA mutation [44] SNPs in TLR3, TLR7, TLR8 Liver Infection Hepatitis C virus [28] Pri-miR-124-1 and STAT3 Stomach Cancer DNA mutation [49] Monocyte/granulocyte to lymphocyte ratio Liver Cancer DNA mutation [56] Leptin, HOMA Liver Fibrosis He...…”
Section: Kidneymentioning
confidence: 99%